2020
DOI: 10.47577/tssj.v9i1.954
|View full text |Cite
|
Sign up to set email alerts
|

Social Integration and Psychological Wellbeing in a Sample of the Swedish-speaking Minority of Western Finland

Abstract: The role of social integration in determining subjective psychological wellbeing in a sample of Swedish-speaking Finns in Ostrobothnia was investigated. A questionnaire was completed by 298 respondents (208 females, 90 males). The mean age was 32.7 years (SD 13.4) for females and 28.9 years (SD 13.4) for males. The age span was between 16 and 90 years. The questionnaire consisted of four scales measuring social integration. Females scored significantly higher on access to social benefits, positive social relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Sex differences in the four scales measuring social integration (Access to Social Benefits, Satisfaction with the Neighborhood, Positive Social Relations, and Trust in the Finnish Judiciary System) have been reported elsewhere (Grigaitytė et al, 2020) and will accordingly not be reported here. Sex differences in the three scales measuring proactive attitudes towards the integration of immigrants (Cultural Efforts, Structural Efforts, and Openness to Diversity) have likewise been reported elsewhere (Grigaitytė et al, 2019).…”
Section: Sex Differencesmentioning
confidence: 86%
See 1 more Smart Citation
“…Sex differences in the four scales measuring social integration (Access to Social Benefits, Satisfaction with the Neighborhood, Positive Social Relations, and Trust in the Finnish Judiciary System) have been reported elsewhere (Grigaitytė et al, 2020) and will accordingly not be reported here. Sex differences in the three scales measuring proactive attitudes towards the integration of immigrants (Cultural Efforts, Structural Efforts, and Openness to Diversity) have likewise been reported elsewhere (Grigaitytė et al, 2019).…”
Section: Sex Differencesmentioning
confidence: 86%
“…Social integration was assessed with four subscales: Access to Social Benefits (8 items, α = .83), Satisfaction with the Neighborhood (8 items, α = .82), Positive Social Relations (4 items, α = .72), and Trust in the Finnish Judiciary System (7 items, 9α = .80). The scales are presented in detail in Grigaitytė, Österman, Björkqvist (2020). Some sample items are presented in brackets in the following: Access to Social Benefits ("I can easily receive an education", "I can easily access public services such as hospitals, police, FPA (KELA) etc.…”
Section: Instrumentmentioning
confidence: 99%
“…Lokus kendali juga menjadi moderator antara stres yang dirasakan dengan kesejahteraan psikologis seseorang (Xia & Ma, 2020). Sejalan dengan Grigaitytė et al (2020)…”
unclassified